“Pasyje amorata”, or signs of linguistic fashion in the literature of the House of Wettin period - Maciejewska, Iwona (Papers in Linguistics, 2019)
The aim of the discussion presented in the article was to draw attention to a linguistic fashion which spread in the first half of the 18th century and manifested itself in the use of the previously non-occurring Polish words amorat (a male lover, admirer, seducer) and amoratka (a female lover, admirer, seducer), as well as the popularity − influenced by the French language − of the word pasyja in its new meaning of “passion”. A linguistic frequency analysis of various-genre texts from that period, conducted as part of research into the manner of presenting the topic of love and eroticism in the House of Wettin era, demonstrates that in the face of the changes in morality and mentality, new possibilities were sought to express emotions. The language of feelings evolved under the influence of, inter alia, the popularity of specific literature, first of all romance novels (primarily translations from French or Italian), which were read, written and translated by both men and women, the latter taking up literary activity on such a scale for the first time in history. The conducted research was aimed at broadening the contemporary knowledge of the late-baroque Polish language and enlarging the corpus of excerpts for the ongoing work on the Dictionary of the Polish Language in the 17th Century and the First Half of the 18th Century. At the same time, the research demonstrated that the phenomenon of a linguistic fashion also applies to the language of the past, and the vocabulary occurring in literary works influenced other genres of writing, such as the letter, diary or memoir.